2016
DOI: 10.3390/molecules21080994
|View full text |Cite
|
Sign up to set email alerts
|

Computational Approaches to Toll-Like Receptor 4 Modulation

Abstract: Toll-like receptor 4 (TLR4), along with its accessory protein myeloid differentiation factor 2 (MD-2), builds a heterodimeric complex that specifically recognizes lipopolysaccharides (LPS), which are present on the cell wall of Gram-negative bacteria, activating the innate immune response. Some TLR4 modulators are undergoing preclinical and clinical evaluation for the treatment of sepsis, inflammatory diseases, cancer and rheumatoid arthritis. Since the relatively recent elucidation of the X-ray crystallograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 87 publications
(112 reference statements)
4
76
0
2
Order By: Relevance
“…The lipid A moiety is localised in the outer cell membrane and is formed from a 1,4-bis-phosphorylated diglucosamine molecule linked to variable acyl chains (e.g., six chains in Escherichia coli LPS) [ 27 , 29 ]. The phosphate groups and acyl chains of LPS are important for interactions with TLR4, and alterations in these can shift the molecule from being an agonist to an antagonist [ 27 , 31 ]. LPS may not be the only ligand for TLR4 as damage-associated molecular patterns (DAMPs), such as high-mobility group box 1 (HMGB1) and heat shock proteins (HSPs), have also been suggested to be capable of inducing activation through this receptor [ 12 , 32 ].…”
Section: Tlr4 Signalling In Nucleated Cellsmentioning
confidence: 99%
“…The lipid A moiety is localised in the outer cell membrane and is formed from a 1,4-bis-phosphorylated diglucosamine molecule linked to variable acyl chains (e.g., six chains in Escherichia coli LPS) [ 27 , 29 ]. The phosphate groups and acyl chains of LPS are important for interactions with TLR4, and alterations in these can shift the molecule from being an agonist to an antagonist [ 27 , 31 ]. LPS may not be the only ligand for TLR4 as damage-associated molecular patterns (DAMPs), such as high-mobility group box 1 (HMGB1) and heat shock proteins (HSPs), have also been suggested to be capable of inducing activation through this receptor [ 12 , 32 ].…”
Section: Tlr4 Signalling In Nucleated Cellsmentioning
confidence: 99%
“…In this regard, Mancek-Keber and Jerala [148] have proposed three postulates to distinguish direct agonists from indirect activators: (1) the agonist requires the TLR-4/MD-2 receptor complex; (2) either synthetically or in situ, they must activate the receptor complex in order to eliminate artefacts from other agonists; and (3) a specific molecular interaction between the agonist and TLR-4/MD-2 must be identified. Furthermore, in 2016 the group of Martin-Santamaria [149,150] proposed to use computational approaches [149] and big databases [150] for the identification of all atomic details in the TLR-4 receptor structure itself and the ligand-receptor interactions of different modulators to develop novel agonists and antagonists with promising biomedical applications, to reduce toxic effects, and improve drug-like properties, fine-tuning of relative potency of agonists and antagonists, binding capacity and specificity.…”
Section: Therapeutic Role Of Tlr-4 Pathway: From Experimental Data Tomentioning
confidence: 99%
“…Studies have reported direct involvement of SP-A in TLR2 signalling, and inhibition of downstream gene activation (Murakami et al 2002). SP-A interacts directly with TLR4 and myeloid differentiation factor 2 (MD-2), which are known critical signalling receptors for LPS (Billod et al 2016). Thus, binding of SP-A with extracellular domain of TLR4 and MD-2 was revealed in a calcium-dependent manner, involving the CRD region.…”
Section: Collectin (And C1q) Receptorsmentioning
confidence: 99%